Export Promotion Incentives (Instrument of Economic Growth - Batra, Bhawana (Journal of Commerce and Trade, 2011)
Export promotion was recognized as one of the important objectives of the Five Year plans. Various supporting measures like the export entitlement scheme, the duty drawback scheme, export promotion capital goods Scheme etc. were introduced. Exports are the result of a series of steps which include improved technology of production, financial arrangement, export marking, packing, consumer preferences in the buyer countries, disadvantage in pricing due to domestic factors such as internal taxation, import restrictions, high prices of indigenous raw material or poor quality of locally available material. Most developing countries have resorted to a number of export promotion measures. With a view to make exports an effective instrument for promoting greater economic activity and employment a number of schemes which have been in existence for some time now are strengthened and improved. our export promotion measures should be directed towards the realisation of the end of creating right commerical image. Exprots are vital for self-sustined growth, and therefore export promotion incentives should be considered as a base of international trade of the country. for which the need of the hour is a long term export strategy.